Health outcomes for children born to teen mothers in Cape Town, South Africa() - Branson, Nicola (Econ Dev Cult Change, 2015)
This paper analyzes whether children born to teen mothers in Cape Town, South Africa are disadvantaged in terms of their health outcomes because their mother is a teen. Exploiting the longitudinal nature of the Cape Area Panel Study, we assess whether observable differences between teen mothers and slightly older mothers can explain why first-born children of teen mothers appear disadvantaged. Our balanced regressions indicate that observed characteristics cannot explain the full extent of disadvantage of being born to a teen mother, with children born to teen mothers continuing to have significantly worse child health outcomes, especially among coloured children. In particular, children born to teens are more likely to be underweight at birth and to be stunted with the disadvantage for coloured children four times the size for African children.